Estudio De Caso: Comportamiento Mecanico Del Hierro Fundido Gris Perlitico Sometido Al Fenómeno De Termofluencia - Reyes, Jorge Isaías Caicedo; Chávez, Javier Enrique Orna; Dávila, Eduardo Segundo Hernández (European Scientific Journal, ESJ, 2017)
The application of foundries has been extended in recent times due to the advancement in casting and cooling techniques. This leads to a better control of their mechanical properties by allowing them to replace steel in multiple applications. In this work, the results of an experimental study that seeks to obtain information on the combined effect of tension (1224 Kgf / cm2) and temperature (500, 550, 600 and 650 ° C) in the pearlitic gray cast iron was addressed. The methodology used is analytical, qualitative, quantitative, deductive, and experimental logic. The tests were carried out according to the ASTM E139 standard using flat specimens of reduced section sized according to ISO 6892: 1998 (E). From the specimens tested, specimens were extracted from the fractured area to perform metallographic and microhardness tests. The results showed that for the temperatures of 500, 550 and 600°C, no complete curves characteristic of the creep phenomenon were obtained, while at 650°C, the curve obtained was complete. Regarding the metallographic study, it did not present a considerable degradation at the different study temperatures despite reaching the fracture in all cases. From the study of the hardness, a similar behavior was obtained in the curves for all the specimens as measurements were made moving away from the fracture.